Satisfaction With the Self-Assessment of University Students Through e-Coping With Academic Stress Utility (TM) - Fuente, Jesús de la; Martínez-Vicente, José Manuel; Peralta-Sánchez, Francisco Javier; González-Torres, María del Carmen; Artuch-Garde, Raquel; Garzón-Umerenkova, Angélica (Frontiers in Psychology, 2019)
The general purpose of this report is: (1) research was to check whether the degree of satisfaction with the self-assessment activity of university students was related to the scores obtained and the degree of different variables, associated with level of Self-Regulation; (2) to present the online utility, e-Coping with Academic Stress (TM), as a technological development in Educational Psychology; (3) analyze the possibilities of transfer of this technological innovation. A total of 929 university students, coming from a public university, participated in the use of this online utility. University students can use the tool's online inventories to make self-assessments in the different variables of Studying, Learning and Performing under Stress (SLPS Competency Model). Descriptives, correlational and inferential analyzes (ANOVAs and MANOVAs) were carried out. The results allowed to know the profile of competences of the analyzed university students, in addition to the degree of satisfaction with the self-evaluation. Finally, we communicate possible actions and options available for transfer of this resulting technology, through RD transfer contracts arranged directly or with other universities.
Keywords: SLPS Competency Model; university academic stress; e-technological development; innovation transfer; validation study; JCR; Scopus